Farmers’ Attitudes toward Urbanization Pressure for Agriculture Sustainability - Mulya, Setyardi Pratika; Hudalah, Delik; Prilandita, Niken (Universitas Muhammadiyah Yogyakarta, 2025)
Farmers’ attitudes are closely related to intrinsic and extrinsic factors in carrying out agricultural activities. Meanwhile, socio-economic characteristics, spatial aspects, values, agricultural attributes, and biophysical assets are tools for understanding the complex relationships between various factors influencing behavior. Urbanization pressure is one of the external factors affecting farmers’ attitudes toward maintaining land and agricultural activities. Therefore, this study aims to clarify the relationship between regional characteristics and farmers’ attitudes, as well as the factors influencing attitudes toward maintaining agriculture at different levels of urbanization pressure. This study utilized a global narrative or integrative literature review combined with in-depth interviews with farmers and agricultural officers to expand the local context. The results disclosed that farmers experienced challenges in maintaining four key factors in facing urbanization pressure, encompassing land, activities, production, and productivity. Regional characteristics influenced by urbanization have played a crucial role in shaping farmers’ attitudes. Farmers required support from the government, academics, entrepreneurs, and the community in facing the increasingly rapid urbanization pressure.